y g y f clearly result of g y f further

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: the definition the Convolution x, y (b) have (u(!) y ) =(g (y )f (! ). Clearly )ˆ result) of g (y )f (! ). Further, that part(a) and to ˆ ˆ ,integral on theZ rightyconvergesy = Z the Fourier Transform any (x) uy (! , sinceto x does not exist for of f Z The first the Fourier Transform of u(x, ) with respect Theorem we have x ˆ 4. Letvalue,yt) howeverx, t)} (x)g (y )e(x, t)dxi= dx. )(this f (x)e i x dx = g (y )fSince u(! (x, y F{u ˆ u ix F{u of =. )} =( the f = g (y exists, y second integralediverges Z was shown in class). (! ). i 1 Z Z Z (x z ) ( ˆ F( 1) f (! )e Transform xto integral obtain tx }} = ApplyyFourierthist } = Fi the PDE )}F{ thei left divergesffor any xz t) dz y and t). g { 6= 0, means {F{f (x to on (x ) value of = f (x (b) (f (x) + g (y ))e dx = f ( x) e dx + g (y ) e i dx. the Fourier Tranform of u(x, y ) does not exist. ˆ + ut + t ˆ ˆ The first integral i! utheZright u = 0 x since the Fourier Transform of f (x) converges Z on 4. Let u(! , t) = F{u(x, t)} = ˆ u(x, t)e i dx. i 3. (a) exists, however the second)integral diverges,!usingwas shown in class). Since F{ (x a)} = (x a e ut x dx = (t + a (this the substitution property. e i i )ˆ ˆ= u Apply Fourier Transform to PDE to obtain g (y ) 6= 0, this means the integral on the left diverges for any value of y and ˆ (b) Let F{f (x)} = f (! ). Using the result of part(a) and the Convolution the Fourier Tranform+ uu+ tu) = 0 not exist. i! u ofˆt (x, y does ˆ ˆ1 Theorem we have Z i ˆ= u 3. (a) F{ 1 (x a)} =t (x a)e ut x dx = (t + ai,! )ˆ Z the substitution property. e i using ˆ F {f (! )e i } = F 1 {F{f (x)}F{ (x t)}} = f (x z ) (z t) dz = f (x t). ˆ(! ). Using the result of part(a) and the Convolution (b) Let F{f (x)} = f Z 1 4. LetTheorem we have t)} = u(! , t) = F{u(x, ˆ u(x, t)e i x dx. Z Apply 1 {f (! )e Transform 1to PDE )}F{ (x t)}} = Fourier i t } = F {F{f (x to obtain ˆ F f (x z ) (z t) dz = f (x t). Z 1 i! x AMATH Z t i! x Assignment i! u + Zˆt + tu = 0 ˆu ˆ x 4. Let u(! , t) = F{u(x, t)} = ˆ uux, t)e i (tdx...
View Full Document

This document was uploaded on 02/09/2014.

Ask a homework question - tutors are online